(untitled) (Pedagogical Horizons, 2021)
The ancient term of leisure is described and commented on in its historical context, guided by literature. References by Aristotle, Seneca, Goethe, Pestalozzi, Rainer Maria Rilke, Martin Wagenschein and Hannah Arendt support the substantive framework for a semantic topicality and current relevance of this term. The discussion about its plausible adaptation for the practical school field leads to a realistic model of the interlinking of work and leisure.